2009
DOI: 10.1016/j.acra.2008.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation

Abstract: Rationale and Objectives Inflammatory reaction surrounding the ablated area is a major confounding factor in the early detection of viable tumor after radiofrequency (RF) ablation. A difference in the responsiveness of normal and tumor blood vessels to vasoactive agents may be used to distinguish these regions in post-ablation follow-up. The goal of this study was to examine longitudinal perfusion changes in untreated viable tumor and the peripheral hyperemic rim of RF-ablated tumor in response to a vasoconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…We found blood volume and blood flow in BPE decreased on day 1 and increased on days 4 and 7 after ablation. Histology changes in the same tumor model on days 2 and 7 after RF ablation were reported in our previous study (Wu et al 2009). In short, the peripheral rim of ablated tumor presented with a hyperemic reaction with dilated vessels and congestion on day 2 after ablation and numerous inflammatory vessels and granulation tissue formation on day 7.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We found blood volume and blood flow in BPE decreased on day 1 and increased on days 4 and 7 after ablation. Histology changes in the same tumor model on days 2 and 7 after RF ablation were reported in our previous study (Wu et al 2009). In short, the peripheral rim of ablated tumor presented with a hyperemic reaction with dilated vessels and congestion on day 2 after ablation and numerous inflammatory vessels and granulation tissue formation on day 7.…”
Section: Discussionsupporting
confidence: 66%
“…However, this border became less distinct over time. This is most likely due to the typical inflammatory response and granulation tissue formation after RF ablation (Wu et al 2009). However, it was difficult to differentiate BPE from residual tumor by visual judgment alone due to contrast enhancement in both regions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a critical liposome size exists below which active targeting substantially improves the intratumoral retention of nanoparticles, especially at slow blood flow regions. Thus, the use of an easily measured phenotypic biomarker (tumor blood flow) 41, 58, 59 could facilitate the selection of a specific set of different nanoparticles to maximize the overall deposition into a specific tumor. This implies that therapeutic regimens could be individualized to the regional hemodynamic profile of a patient’s tumor to maximize the drug deposition in a tumor not just on a patient-by-patient but on a region-by-region basis.…”
Section: Resultsmentioning
confidence: 99%
“…Even in these ‘controlled’ tumor models of the same cell type, stage, and tumor size, regions with very different blood flows were identified which varied widely in topology from one tumor to the next, which is consistent with previous studies. 40, 41 While nCE-μCT provided high resolutions, it only allowed to study the intratumoral deposition of a single liposome formulation. Therefore, we utilized small animal fluorescence imaging (FMT) to quantitatively and simultaneously image four different liposome formulations (labeled with a different NIR fluorophore) in the same tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was recently shown that the intravascular and transvascular transport of nanoparticles in a tumor’s region is strongly governed by the relationship of particle size to the microvascular network and hemodynamics of that tumor’s region [38]. Given that tumors are heterogeneous in both hemodynamics and pathology [35, 3944], a single “one-size-fits-all” nanoparticle design might not be the most effective approach. We suggest that the nanoparticle design depends on the exact location of interest (e.g.…”
Section: Introductionmentioning
confidence: 99%